ACTIVITIES OF REGIONAL HEAD DIRECTIONS ON SOCIAL MEDIA IN HANDLING THE COVID-19 PANDEMIC - H, Maulana Danar Maaliki; Suwandi, Sarwiji; Sumarwati, Sumarwati (ppjbsip, 2022)
This research was motivated by the occurrence of the Covid-19 virus which first entered Indonesia in early 2020 and was designated as a pandemic. The spread is very fast and is a very dangerous outbreak, in July 2021 Indonesia experienced a second wave of the Covid-19 pandemic. Therefore, regional heads are people who have an important role in handling the Covid-19 pandemic in an area. Often regional heads during the handling of the Covid-19 pandemic carry out preventive activities and post them on social media. Researchers are interested in researching posts from the regional head related to the study of directive speech acts. This research is a qualitative descriptive research with content analysis approach. The source of the data used is a video document on the social media account of Ganjar Pranowo who is the head of the Central Java region and the informant is an Indonesian language teacher at SMP Negeri 4 Surakarta and SMP Negeri 20 Surakarta. Data collection techniques used are document analysis and interviews. The validity of the data using theoretical triangulation techniques and triangulation of data sources. Data analysis using flow analysis. Based on the results of this study, it aims to describe: (1) the forms, (2) the function of the regional head's directive speech act on social media in handling the Covid-19 pandemic, (3) the use of the results of the analysis of the form and function of the directive speech act in learning Indonesian in junior high school.